(untitled) (Research, Society and Development, 2020)
The objective of this study was to verify the factors that led to the premature interruption of the therapeutic process of a teenager pacient of a school-service of Pshycology of a private University located on the interior of Rio Grande do Sul-RS. The adopted methodoly was a unique and systematic study of case, with exploratory character. As a result, it was verified that factors as the pacient not having available hours that matched the hours of the school-service, lack of family adherence in the treatment and low therapeutic aliance have influenced in the premature abandonment. It is concluded that is necessary to take into account the factors that influence the interruption of treatment, having a deep and broad look at the most diverse aspects.